Elliptic Problems in Curved Domains Using Cubature Points Based Triangular Spectral Elements and Isoparametric Mappings (Journal of Mathematical Study, 2020)
Using the cubature points based triangular spectral element method andisoparametric mappings, we provide accuracy results for elliptic problems in non polygonal domains. Two regimes of convergence, associated to the bulk and to the boundaryof the computational domain are clearly discerned and an efficient way to define theisoparametric mapping is proposed.
Keywords: Spectral element method; triangular elements; curved domains; isoparametric mappings; cubature points; diagonal mass matrix.